Energy budget and carbon footprint in a wheat and maize system under ridge furrow strategy in dry semi humid areas - Changjiang Li (Nature Portfolio, 2021)
Abstract The well-irrigated planting strategy (WI) consumes a large amount of energy and exacerbates greenhouse gas emissions, endangering the sustainable agricultural production. This 2-year work aims to estimate the economic benefit, energy budget and carbon footprint of a wheat–maize double cropping system under conventional rain-fed flat planting (irrigation once a year, control), ridge–furrows with plastic film mulching on the ridge (irrigation once a year, RP), and the WI in dry semi-humid areas of China. Significantly higher wheat and maize yields and net returns were achieved under RP than those under the control, while a visible reduction was found for wheat yields when compared with the WI. The ratio of benefit: cost under RP was also higher by 10.5% than that under the control in the first rotation cycle, but did not differ with those under WI. The net energy output and carbon output followed the same trends with net returns, but the RP had the largest energy use efficiency, energy productivity carbon efficiency and carbon sustainability among treatments. Therefore, the RP was an effective substitution for well–irrigated planting strategy for achieving sustained agricultural development in dry semi-humid areas.